Three-pion Bose-Einstein correlations measured in proton-proton collisions - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract A study on the Bose-Einstein correlations for triplets of same-sign pions is presented. The analysis is performed using proton-proton collisions at a centre-of-mass energy of s $$ \sqrt{s} $$ = 7 TeV, recorded by the LHCb experiment, corresponding to an integrated luminosity of 1.0 fb −1. For the first time, the results are interpreted in the core-halo model. The parameters of the model are determined in regions of charged-particle multiplicity. This measurement provides insight into the nature of hadronisation in terms of coherence, being consistent with the presence of coherent emission of pions.